2021
DOI: 10.1038/s41598-021-96098-w
|View full text |Cite
|
Sign up to set email alerts
|

Indoor and outdoor noise changes due to the COVID-19 lockdown and their effects on individuals’ expectations and preferences

Abstract: The COVID-19 pandemic significantly modified our urban territories. One of the most strongly affected parameters was outdoor noise, caused by traffic and human activity in general, all of which were forced to stop during the spring of 2020. This caused an indubitable noise reduction both inside and outside the home. This study investigates how people reacted to this new unexpected, unwanted and unpredictable situation. Using field measurements, it was possible to demonstrate how the outdoor sound pressure leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…These four diagnoses are relatively stable and unlikely to be emergent. People with mild cataract may only suffer from glare and photophobia, which could be managed conservatively by wearing sunglasses or by decreasing outdoor activities, which were also largely decreased during the COVID-19 period [ 34 , 35 ]. Refraction disorders, which mostly consist of myopia control in this study, are emerging problems in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…These four diagnoses are relatively stable and unlikely to be emergent. People with mild cataract may only suffer from glare and photophobia, which could be managed conservatively by wearing sunglasses or by decreasing outdoor activities, which were also largely decreased during the COVID-19 period [ 34 , 35 ]. Refraction disorders, which mostly consist of myopia control in this study, are emerging problems in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was drawn for a university classroom [ 48 ], adopting the post-occupancy evaluation (POE) method [ 47 ]. The response range for the comfort sensation was from 1 to 5 [ 20 ], where 1 is “very poor” and 5 is “very good”. All participation was voluntary at the end of the lecture hour (session).…”
Section: Case Study and Methodsmentioning
confidence: 99%
“…It is widely accepted that a user’s comfort, or indoor environmental quality (IEQ) [ 6 , 7 , 8 ], consists of four core parameters, also known as IEQ elements, IEQ factors, or IEQ categories. These are thermal comfort [ 9 , 10 , 11 , 12 , 13 ], indoor air quality (IAQ) [ 14 , 15 , 16 , 17 ], acoustic comfort [ 18 , 19 , 20 ], and visual comfort [ 21 , 22 , 23 , 24 , 25 , 26 ]. Achieving high IEQ levels could prevent the occurrence of sick building syndrome (SBS) [ 27 , 28 , 29 ], building-related diseases, multiple chemical sensitivities (MCS), and other unrecognized controversial disorders [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such observed quiet residential environment caused by the pandemic led to positive reactions of people towards low noise levels in their neighborhoods, especially in both indoor and outdoor environments. The study found that even the most vulnerable group (> 60 years) was able to detect low indoor noise levels during the pandemic (Caniato et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%